Protective Influence of Elaesis Guineensis Leaf in Diet on Petroleum-Mediated Kidney Damage in Rat - Achuba, F. I. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Herbal medicine is gaining ground these days and the search for simple antidote for crude oil toxicity is ongoing. This was the reason for this study. The study was comprised ninety six female rats divided into six groups of sixteen rats each. Rats in control group were fed with diet without any treatment while rats in groups 2 and 3 were fed with diets treated with known amount of Elaesis guineensis leaf. Rats in group 4 were fed with crude oil contaminated diet. Rats in groups 5 and 6 were fed with contaminated diet mixed with known amount of ground Elaesis guineensis leaf. Biochemical and histological analysis were carried out after three and six months respectively. The results show that pretreatment of crude oil contaminated diet mixed with Elaesis guineensis leaf tend to restore values of lipid peroxidation, xanthine oxidase (XO) activity, superoxide dismutase (SOD) activity and catalase (CAT) activity close to control values. Histological examination indicates protective effect of Elaesis guineensis leaf against deleterious effect of crude oil on the kidney. It is obvious that the leaves of Elaesis guineensis could be used in the treatment of crude oil toxicity. And indeed setting a fresh agenda for further scientific investigations